2019
DOI: 10.1172/jci124793
|View full text |Cite
|
Sign up to set email alerts
|

uPAR isoform 2 forms a dimer and induces severe kidney disease in mice

Abstract: Conflict of interest:JR and SS are inventors on pending and issued patents related to antiproteinuric therapies. They stand to gain royalties from present and future commercialization. They also are cofounders and advisors to TRISAQ, a biotechnology company. CW has a pending patent on suPAR in diabetes. He stands to gain royalties from future commercialization products concerning this application (see Supplemental Data for complete information).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 35 publications
3
63
0
1
Order By: Relevance
“…Inflammation and oxidative stress are central components of the pathogenesis of acute kidney injury, implicating multiple subtypes of immune cells. 8,9 Evidence of a pathway linking the bone marrow to kidney injury has emerged, involving soluble urokinase plasminogen activator receptor (suPAR) 7,[10][11][12][13][14][15][16][17] -the circulating form of a glycosylphosphatidylinositol-anchored three-domain membrane protein. This receptor is normally expressed at very low levels on a variety of cells, including endothelial cells, podocytes, and, with induced expression, immunologically active cells such as monocytes and lymphocytes.…”
Section: Results-mentioning
confidence: 99%
“…Inflammation and oxidative stress are central components of the pathogenesis of acute kidney injury, implicating multiple subtypes of immune cells. 8,9 Evidence of a pathway linking the bone marrow to kidney injury has emerged, involving soluble urokinase plasminogen activator receptor (suPAR) 7,[10][11][12][13][14][15][16][17] -the circulating form of a glycosylphosphatidylinositol-anchored three-domain membrane protein. This receptor is normally expressed at very low levels on a variety of cells, including endothelial cells, podocytes, and, with induced expression, immunologically active cells such as monocytes and lymphocytes.…”
Section: Results-mentioning
confidence: 99%
“…From a translational perspective, this domain flexibility also proved essential for the development of a small 9-mer peptide targeting an intermediate conformation in uPAR [28,36] and this assisted its further maturation into a PET-probe currently used for non-invasive imaging of uPAR expression in patients with malignant solid tumors [37][38][39]. Moreover, the dimer of uPAR isoform 2 was reported to induce kidney diseases in mice [40].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…). Note that these msuPAR2‐Tg mice acquired a renal pathology characteristic of FSGS . Taken together, these findings indicate that although an elevated circulating suPAR level causes kidney glomerular sclerosis, it does not lead to any obvious liver fibrosis in mice.…”
Section: Role Of Supar In the Management Of Liver Diseasementioning
confidence: 53%
“…Moreover, as a biomarker, we found that baseline suPAR levels predict the incidence and progression of chronic kidney disease . To uncover the mechanisms underlying the multifaceted functions of suPAR in kidney disease, we developed two suPAR transgenic (Tg) mouse models, msuPAR1‐Tg for uPAR isoform 1 (canonical form) and msuPAR2‐Tg for isoform 2 (secreted form), in which suPAR is driven by adipocyte protein 2 (AP2) promoter and released into blood circulation thereafter . With circulating suPAR evidently increased in both msuPAR‐Tg models, we examined liver tissues for any functional and histological changes.…”
Section: Role Of Supar In the Management Of Liver Diseasementioning
confidence: 99%